Theosophical concept of education in Bronisław F. Trentowski’s pedagogy = Teozoficzna idea (wy)kształcenia w pedagogice Bronisława F. Trentowskiego - Stępkowski, Dariusz (Przegla̜d religioznawczy, 2020)
Bronisław F. Trentowski presented in Chowanna the first systemic concept in Polish language of pedagogy as a science of education. The fundamental role was determined to the Polish term "(wy)kształcenie", ie. education, which at that time was only entering the professional language of pedagogy. Its theosophical genealogy will be traced using the examination of the primary and secondary written sources. The paper consists of three sections. In the first section, the concept of Trentowski’s theosophy will be outlined. On this basis, the second section explains the use of the explored term in Chowanna, Trentowski’s main pedagogical work. The third part draws attention to the consequences resulting from theosophical interpretation of the concept of the Polish term "(wy)kształcenie" in Trentowski’s pedagogy.